Building a system of supplementary exercises under the direction of student capacity development in relation to teaching pronouns at schools - Thu Phuong, Nguyen (VNU Journal of Science: Education Research; Vol 34 No 2DO - 10.25073/2588-1159/vnuer.4149, 2018)
Based on the requirements of teaching Vietnamese under the direction of student capacity building, with the use of surveys and evaluation of questions and exercises for teaching pronouns in the current Vietnamese textbooks for Grade 5, this paper proposes a system of questions and exercises towards student capacity building in teaching pronouns at primary schools. Such exercises are developed in order to not only help students with knowledge of pronouns, the culture of addressing people in communication using Vietnamese but also provide students with new communication contexts and situations for practice, which in turn will help students use pronouns that are culturally suitable with the way Vietnamese people address people in communication.